Rethinking egocentric bias: A computer mouse-tracking study of adult belief processing - O'Connor, Richard J.; Lucas, Andrew; Riggs, Kevin J. (Journal of experimental psychology. General, 2024)
Several theories of belief processing assume that processing another's false belief requires overcoming an egocentric bias toward one's current knowledge. The current evidence in support of this claim, however, is limited. In order to investigate the presence of egocentric bias in adult belief processing, computer mouse tracking was used across three experiments to measure attraction toward response options reflecting one's current knowledge while reporting a false belief. Participants viewed scenarios in which an agent either had a true belief or a false belief about the location of a set of keys. Participants used a mouse to answer reality questions "where are the keys currently hidden?" and belief questions "where does she think the keys are?" Mouse-tracking measures indexing attraction toward response options during decision making were measured, along with time taken to make a response and accuracy. Experiment 1 found no evidence, in any measures, that participants showed a bias toward their own knowledge when reporting another's false belief. Experiment 2 investigated whether differences in event timings between true belief and false belief scenarios in Experiment 1 masked an egocentric bias. Experiment 3 investigated whether the lack of egocentric bias could be explained by participants prioritizing encoding the other's beliefs. Neither follow-up experiment found evidence supporting the presence of an egocentric bias. Overall, contrary to many theories of belief processing, our results suggest that adults are readily able to process other people's beliefs without having to overcome a default bias toward their own knowledge. (PsycInfo Database Record (c) 2024 APA, all rights reserved).
Keywords: Automaticity; Theory of mind; False belief; Egocentric bias; Adult belief processing; Mouse tracking